2011
DOI: 10.1111/j.2042-7158.2010.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and chemical composition of the essential oil of Hofmeisteria schaffneri

Abstract: The composition and antimicrobial activity of the oils changed slightly from flowering to non-flowering seasons. The results of the present investigation provide in-vitro scientific support for the use of the plant against skin infections in Mexican folk medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…S. aureus is a common Gram-positive bacterium that can cause pathogenic conditions including food-borne diseases and infections ranging from minor localized skin disturbances to life-threatening deep tissue and systemic illness. Different components of EOs obtained from Alpinia pahangensis , Origanum vulgare , Origanum dictamnus , Mentha piperita , Lavandula hybrida , Zataria multiflora and Hofmeisteria schaffneri have been tested against S. aureus , and all were found to possess potential inhibitory activity [ 30 , 31 ]. Furthermore, combination of essential oil with an antimicrobial agent produces a synergistic effect against multidrug-resistant S. aureus , and in many cases, a substantial decrease in the MIC has been observed [ 32 ].…”
Section: Antimicrobial Activity Of Essential Oilsmentioning
confidence: 99%
“…S. aureus is a common Gram-positive bacterium that can cause pathogenic conditions including food-borne diseases and infections ranging from minor localized skin disturbances to life-threatening deep tissue and systemic illness. Different components of EOs obtained from Alpinia pahangensis , Origanum vulgare , Origanum dictamnus , Mentha piperita , Lavandula hybrida , Zataria multiflora and Hofmeisteria schaffneri have been tested against S. aureus , and all were found to possess potential inhibitory activity [ 30 , 31 ]. Furthermore, combination of essential oil with an antimicrobial agent produces a synergistic effect against multidrug-resistant S. aureus , and in many cases, a substantial decrease in the MIC has been observed [ 32 ].…”
Section: Antimicrobial Activity Of Essential Oilsmentioning
confidence: 99%
“…9) Essential oil-containing formulation exhibited antimicrobial activity against Gram-negative and Gram-positive bacteria. 10) Recently, fatty acid-loaded liposomes were found to efficiently inhibit P. acnes growth by directly fusing into bacterial membranes and releasing the acid cargo. 11) Lipid-based vehicle systems such as emulsions and microemulsions are modern colloidal carriers for dermal drug delivery.…”
mentioning
confidence: 99%
“…The infusion and essential oil showed good activity in these evaluations; phytochemical analysis of both preparations revealed the presence of thymol derivatives 15: hofmeisterin III (1), 8,9-epoxy-10acetoxythymol angelate (2), thymol isovalerate (3), thymol isobutyrate (4), and 8,9-epoxy-10-hydroxythymol angelate (5) [1,3]. GC-FID analysis of the essential oil revealed that compounds 1 and 2 were the most abundant [2]. In order to complete the preclinical efficacy studies of H. schaffneri, we now report the spasmolytic effect of both preparations and major components using an in vivo mouse gastrointestinal transit test [4].…”
mentioning
confidence: 90%
“…The curative properties attributed to the plant prompted us to carry out the evaluation of its effects as an antinociceptive and antimicrobial agent [1,2]. The infusion and essential oil showed good activity in these evaluations; phytochemical analysis of both preparations revealed the presence of thymol derivatives 15: hofmeisterin III (1), 8,9-epoxy-10acetoxythymol angelate (2), thymol isovalerate (3), thymol isobutyrate (4), and 8,9-epoxy-10-hydroxythymol angelate (5) [1,3]. GC-FID analysis of the essential oil revealed that compounds 1 and 2 were the most abundant [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation